DEVELOPING COGNITIVE ABILITY TO MATCHING NUMBERS AND SYMBOL USING A COMBINATION OF MODELS, METHODS, AND MEDIA LEARNING - Erviana, Raydesi; Ahmad, Karyono Ibnu; Sari, Nina Permata (Journal of K6, Education and Management, 2019)
This study aims to determine the activities of teachers, children, and the results of children's cognitive development. The approach used is a qualitative research approach and with the type of classroom action research, which was carried out in 4 meetings, research settings in group A children in Aisyiyah Kindergarten, Kecamatan Satui, Kabupaten Tanah Bumbu, amounting to 15 children. Data collection techniques using observation, documentation and interviews and assessment of aspects of cognitive development. The results showed that the teacher's activity at the 4th meeting with a score of 36 in the category of Very Good. Children's activities at the 4th meeting with a percentage of 87.5% the category is very active and the results of cognitive development at the last meeting reached 84% of children who succeeded by getting «««and ««««. Based on the results of the study it can be concluded that the application of a combination of Picture and picture models, talking sticks, with the method of conversing, demonstration and media card numbers can develop the activities of teachers, children and cognitive development results with very good and very active developing categories.